Himalayan Dreaming Australian mountaineering in the great ranges of Asia, 1922-1990 - Steffen, Will (ANU Press, 2010)
How did climbers from the world's flattest, hottest continent become world-class Himalayan mountaineers, the equal of any elite mountaineer from countries with long climbing traditions and home ranges that make Australia's highest summit look like a suburban hill? This book tells the story of Australian mountaineering in the great ranges of Asia, from the exploits of a brash, young colonial with an early British Himalayan expedition in the 1920s to the coming of age of Australian climbers in the 1980s. The story goes beyond the two remarkable Australian ascents of Mt Everest in 1984 and 1988 to explore the exploits of Australian climbers in the far-flung corners of the high Himalaya. Above all, the book presents a glimpse into the lives - the successes, failures, tragedies, motivations, fears, conflicts, humor, and compassion - themselves to the ultimate limits of survival in the most spectacular and demanding mountain arena of all.